Patients' and carers' views and expectations about intensive management for moderate rheumatoid arthritis: a qualitative study. Issue 8 (16th November 2016) - Prothero, L.; Georgopoulou, S.; Galloway, J.; Williams, R.; Bosworth, A.; Lempp, H.
Abstract: Intensive management for rheumatoid arthritis (RA) involves frequent hospital visits and adjusted doses or combinations of medication. Research is currently underway to test whether or not intensive management strategies are valuable in moderately active disease, however, patient views on intensive management in this disease group are unknown. The objectives of this study were to explore the views and expectations of patients with moderately active RA and of carers of patients with moderately active RA. We conducted focus groups and one-to-one interviews in 2014 with 14 participants (9 patients, 5 carers) from 4 rheumatology clinics across 3 London Hospital NHS Trusts. Non-English-speaking patients were included with the assistance of a professional translator. Focus groups and interviews were audio recorded and transcribed and transcripts analysed using a framework analysis approach. Four main themes were identified: 'Hopes and Expectations of Intensive Management', 'Acceptability of Intensive Management', 'Patient Education' and 'The Importance of Continuity of Care'. Our main findings were that attendance at frequent clinic appointments was largely acceptable to patients and carers. Views on taking higher doses of medication depended on how stable patients were on their current treatment regime. Continuity of care from the rheumatologist and the provision of written/verbal information about intensive management were important to patients and carers.